The Internalization of Wasathiyah Values In Inclusion Madrasah: A Case Study of Integrated Madrasah Ibtida’iyah of Ar-Roihan Malang - Priatmoko, Sigit (UIN Sunan Kalijaga Yogyakarta, 2019)
The research aim is to comprehensively reveal the construction of Islamic wasathiyah values developed by Integrated Madrasah Ibtidaiyah (IMI) of Ar-Roihan and how these values are internalized into their members. This research used a qualitative approach with a case study design. The methods used to collect data are interviews, observation, and documentation. Data were analyzed using Miles and Huberman's interactive analysis model, which included four stages, namely data collection, data reduction, data presentation, and conclusions drawing. In order to obtain valid data, researchers used source triangulation techniques, triangulation methods, and extension observations. The results showed that the values of wasathiyah at IMI of Ar-Roihan were built based on the contents of the letter ‘Abasa verses 1-10 and the theory of multiple intelligences. This result is by the IMI Ar-Roihan condition, which has a high plurality, which includes the characteristics and needs, intelligence, religious background of students. Based on these two main foundations and plurality, IMI of Ar-Roihan developed eight main wasathiyah values, namely equality, justice, progress, brotherhood, openness, balance, moderate, and tolerance. The eight values are internalized through three curriculum components, namely intracuricular activities, extracurricular activities, and hidden curriculum.